THE ISSUE OF RELEVANCE OF THE SUBJECT OF THE SCHOOL REPERTOIRE IN THE TRAINING OF FUTURE MUSIC TEACHERS - Siddiqov Sodir Sodiqovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article focuses on recommendations to students on the art of singing, ways to develop their performing skills, methods of teaching songs to students. In particular, information about the peculiarities of the science of the school repertoire, the role of the school repertoire in organizing lessons of musical culture, educational and educational possibilities of the school repertoire is covered.